2019
DOI: 10.1002/pits.22235
|View full text |Cite
|
Sign up to set email alerts
|

Family and nonfamily support in relation to burnout and work engagement among Italian teachers

Abstract: Italy had traditionally been considered a family‐oriented culture where support from relatives is primary. The major purpose of this study was to clarify the benefits of social support inside and outside the family for schoolteachers in Italy, focusing on the teacher burnout and work engagement. Findings indicated that the family was by far the most significant source of support. School colleagues who felt close to each other resembled each other in terms of burnout and work engagement. Difficult interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…On the other hand, external support has positive effects on job satisfaction and performance (Halbesleben, 2006;Skaalvik and Skaalvik, 2009;Carlson et al, 2014;McNall et al, 2015). Such findings come from a variety of cultural settings including Spain, Turkey, Korea, Jordan, Israel, Italy, and Palestine (Aycan and Eskin, 2005;Veronese et al, 2018;Fiorilli et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, external support has positive effects on job satisfaction and performance (Halbesleben, 2006;Skaalvik and Skaalvik, 2009;Carlson et al, 2014;McNall et al, 2015). Such findings come from a variety of cultural settings including Spain, Turkey, Korea, Jordan, Israel, Italy, and Palestine (Aycan and Eskin, 2005;Veronese et al, 2018;Fiorilli et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…[1]. Current psychological literature widely addresses the role of teachers' personal resources [2][3][4][5][6][7], relationships with students [8,9], and individual professional resources [10,11] in managing the mentioned challenges. Despite the meaningful role of the teacher's individual contributions to these issues, collaborative practices and strategies seem to better fit such needs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no distinctions were made among the several types of work activity. This could be an important challenge for future research, in the light of a growing literature that highlights how the type of profession or organization can differently impact workers' well-being, their job satisfaction, and the consequent ability to adapt to changes: see, for example, the high risk of burnout for health care professions [101] or for educational contexts, where several studies have shown the central role of different forms of social and familiar support to combat the phenomenon [102][103][104]. Besides, according to this vision, it may also be useful to consider the world of non-profit organizations, subject to continuous forced changes to follow the constant public sector reform movement and in which innovation could be facilitated by an effective strategic management of the intellectual capital [105].…”
Section: Discussionmentioning
confidence: 99%